Cultural Semantics in Translation (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2024)
Cultural Semantics in Translation explores the relationship between language and culture in the process of translation. This theme emphasizes that effective translation goes beyond the linguistic aspect and must consider the cultural context of both the source and target languages. Cultural semantics involves understanding and transferring not only words but also culturally embedded meanings, idiomatic expressions, and societal norms. It addresses challenges such as the absence of direct equivalents between languages, the impact of cultural references, and the need for cultural sensitivity. The work also explores the role of the translator as a cultural mediator and highlights the importance of balancing accuracy with cultural adaptation to ensure the message resonates with the target audience. Through this, the text underscores the significance of translation as a tool for fostering cross-cultural understanding and communication in an increasingly interconnected world.